Pengembangan Blended Learning Mata Kuliah Dinamika Kelompok untuk Mahasiswa Jurusan Bimbingan Dan Konseling - Bambang Dibyo Wiyono; Tamsil Muis; Ari Khusumadewi (Jurnal Bimbingan dan Konseling Terapan, 2018)
Group dynamics is one of the courses contained in the S-1 Guidance and Counseling program. Blended learning is a combination of learning between face-to-face, computer (offline), and internet-based learning (online). The main purpose of blended learning is to provide opportunities for the various characteristics of learners to become self-sustaining, sustainable, and developing throughout life, so that learning will be more effective, more efficient, and more interesting. The development model used in the development process of blended learning of Group Dynamics course is with ADDIE model. The steps of developing this model include: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Development phase that has been done include: analysis, design, development and implementation. Based on expert test results, obtained P = 92.25%, which according to Riduwan (2012) interpretation criteria including the criteria of "very good" and obtain alternative decisions "very feasible". The development of blended learning Group Dynamics has met the acceptability criteria covering aspects of usability, accuracy, and feasibility. However, there should be assistance to students in the implementation of online learning them.